2017
DOI: 10.3892/ol.2017.6629
|View full text |Cite
|
Sign up to set email alerts
|

PCDH8 inhibits glioma cell proliferation by negatively regulating the AKT/GSK3β/β-catenin signaling pathway

Abstract: Protocadherin-8 (PCDH8), a member of the protocadherin superfamily of proteins, is frequently lost in numerous types of cancer. However, the role that PCDH8 serves in human glioma, and the molecular mechanisms underlying this, remain unclear. Data from the present study demonstrated that the expression levels of PCDH8 mRNA and protein were significantly decreased in human glioma tissue compared with normal brain tissue. This suggested that PCDH8 is associated with the development of glioma. Thus, the role of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Currently, there are numerous reports about the close relationship between PI3K/Akt (phosphatidylinositide 3-kinases/protein kinase B) signal pathway and GSK3β [ 42 , 43 , 44 , 45 , 46 ]. Activated Akt can phosphorylate GSK3β resulting in inactivating GSK3β and inhibit the degradation of β-catenin [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are numerous reports about the close relationship between PI3K/Akt (phosphatidylinositide 3-kinases/protein kinase B) signal pathway and GSK3β [ 42 , 43 , 44 , 45 , 46 ]. Activated Akt can phosphorylate GSK3β resulting in inactivating GSK3β and inhibit the degradation of β-catenin [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Most recently, one study showed that the expression levels of PCDH8 were signicantly decreased in human glioma tissues, and restoration of PCDH8 markedly inhibited glioma cell proliferation in vitro. 13 However, the biological roles of PCDH8 in PTC and the related mechanisms remain unclear. Therefore, in the present study, we detected the expression of PCDH8 in human PTC tissues and cell lines, and evaluated its role in PTC progression.…”
Section: -9mentioning
confidence: 99%
“…However, several observations also suggest that the δ-pcdhs regulate the proliferation of neural progenitor cells and the production of neurons (Cooper et al, 2015;Zhang et al, 2014). These results are bolstered by observations implicating the δ-pcdhs as tumor suppressors in a variety of cancers (Xu et al, 2015;Yin et al, 2016;Zong et al, 2017), where forced expression of the δ-pcdhs can inhibit cell proliferation in cancer cell lines. The mechanisms by which δ-pcdhs could regulate proliferation are not known.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases, the loss of δ-pcdh expression correlates with poor prognosis (Bing et al, 2018;Cao et al, 2018;Dang et al, 2016;Lin et al, 2018). In addition, evidence for a tumor suppressive role of the δ-pcdhs has been obtained in vitro, as their forced expression limits tumor growth (Xu et al, 2015;Yin et al, 2016;Zong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%